Fundamentals of fluid mechanics - Munson, Bruce Roy, 1940- (John Wiley & Sons, 2009)
Introduction -- Fluid statics -- Elementary fluid dynamics-the bernoulli equation -- Fluid kinematics -- Finite control volume analysis -- Differential analysis of fluid flow -- Dimensional analysis, similitude, and modeling -- Viscous flow in pipes -- Flow over immersed bodies -- Open-channel flow -- Compressible flow -- Turbomachines.